Image-guided brachytherapy (IGBT) combined with whole pelvic intensity-modulated radiotherapy (WP-IMRT) for locally advanced cervical cancer: A prospective study from Chiang Mai University Hospital, Thailand - Ekkasit Tharavichitkul (2018)
Purpose: A report of preliminary results and toxicity profiles using image-guided brachytherapy (IGBT) combined with whole pelvic intensity-modulated radiation therapy (WP-IMRT) for locally advanced cervical cancer. Material and methods: Fifteen patients with locally advanced cervical cancer were enrolled into the study. WP-IMRT was used to treat the Clinical Target Volume (CTV) with a dose of 45 Gy in 25 fractions. Concurrent cisplatin (40 mg/m2) was prescribed during radiotherapy (RT) on weekly basis. IGBT using computed tomography was performed at the dose of 7 Gy x 4 fractions to the High-Risk Clinical Target Volume (HR-CTV). Results: The mean cumulative doses - in terms of equivalent dose of 2 Gy (EQD2) - of IGBT plus WP-IMRT to HR-CTV, bladder, rectum, and sigmoid colon were 88.3, 85.0, 68.2 and 73.6 Gy, respectively. In comparison with standard (point Aprescription) dose-volume histograms, volume-based image-guided brachytherapy improved the cumulative doses for bladder of 67%, rectum of 47% and sigmoid of 46%. At the median follow-up time of 14 months, the local control, metastasis-free survival and overall survival rates were 93%, 100% and 93%, respectively. No grade 3-4 acute and late toxicities were observed. Conclusion: The combination of image-guided brachytherapy and intensity-modulated radiotherapy improved the dose distribution to tumor volumes and avoided overdose in OARs which could be converted in excellent local control and toxicity profiles.